Advances and Challenges in Antiviral Development for Respiratory Viruses - Luis Adrián De Jesús-González; Moisés León-Juárez; Flor Itzel Lira-Hernández; Bruno Rivas-Santiago; Manuel Adrián Velázquez-Cervantes; Iridiana Monserrat Méndez-Delgado; Daniela Itzel Macías-Guerrero; Jonathan Hernández-Castillo; Ximena Hernández-Rodríguez; Daniela Nahomi Calderón-Sandate; Willy Salvador Mata-Martínez; José Manuel Reyes-Ruíz; et al. (Pathogens)
The development of antivirals for respiratory viruses has advanced markedly in response to the growing threat of pathogens such as Influenzavirus (IAV), respiratory syncytial virus (RSV), and SARS-CoV-2. This article reviews the advances and challenges in this field, highlighting therapeutic strategies that target critical stages of the viral replication cycle, including inhibitors of viral entry, replication, and assembly. In addition, innovative approaches such as inhibiting host cellular proteins to reduce viral resistance and repurposing existing drugs are explored, using advanced bioinformatics tools that optimize the identification of antiviral candidates. The analysis also covers emerging technologies such as nanomedicine and CRISPR gene editing, which promise to improve the stability and efficacy of treatments. While current antivirals offer valuable options, they face challenges such as viral evolution and the need for accessible treatments for vulnerable populations. This article underscores the importance of continued innovation in biotechnology to overcome these limitations and provide safe and effective treatments. Combining traditional and advanced approaches in developing antivirals is essential in order to address respiratory viral diseases that affect global health.